RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND HYPERTENSION LEVELS WITH OSTEOARTHRITIS IN THE ELDERLY USING WOMAC (The Western Ontario And Mcmaster Universities Osteoarthritis Index) - Agus Priyanto; Alvin Abdillah; Luluk Fauziyah Januarti Januarti (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Osteoarthritis is one _ disease joints usually degenerative _ happens with age further , marked with solving cartilage , change bone joints , damage bone joints , damage to tendons and ligaments . The risk factors for osteoarthritis are divided into 2, primary and secondary, one of which is physical activity and level of hypertension. The occurrence of osteoarthritis has an impact on limitations in social and spiritual interactions, decreased physiological abilities, decreased productivity, and psychological disorders. This study aims to analyze the relationship between physical activity and the level of hypertension with the incidence of osteoarthritis in the elderly using WOMAC. This study uses correlation analysis with a cross sectional approach . The independent variables are physical activity and the level of hypertension and the dependent variable is the incidence of osteoarthritis . The total population of this study was 184 elderly with a sample size of 34 elderly using purposive sampling technique . The instruments used were the observation sheet and the WOMAC questionnaire . The results showed that p value 0.436 > Î± 0.05 with this value indicating that there is no relationship between physical activity and the incidence of osteoarthritis in the elderly and also obtained test results showing that there is a relationship between the level of hypertension and the incidence of osteoarthritis in the elderly with a p value value 0.002 < Î± 0.05. So it can be concluded that there is no relationship between physical activity and the incidence of osteoarthritis in the elderly , but there is a relationship between the level of hypertension and the incidence of osteoarthritis in the elderly using WOMAC.It is recommended for the public to better maintain an ideal body weight, diet, lifestyle and not too strenuous physical activities and exercise to reduce pain in the knee joints.